Revision of the genus Chordodes (Gordiida, Nematomorpha) from Africa. II. Ultrastructural redescription of C. africanus Sciacchitano, 1933, C. hawkeri Camerano 1902; C. sandoensis, Sciacchitano 1937; C. schoutedeni, Sciacchitano 1933 and reinterpretation of Chordodes butensis Sciacchitano, 1937 - Zanca, Fernanda; Schmidt-Rhaesa, Andreas; de Villalobos, Cristina; Achiorno, Cecilia (Zootaxa, 2006)
We reinvestigate five African species of the genus Chordodes in order to certify the taxonomic descriptions and verify the species status. By scanning electron microscopy, we demonstrate characteristic cuticular patterns for the species Chordodes africanus, C. hawkeri, C. sandoensis and C. schoutedeni. The fifth species, C. butensis, is synonymized with C. africanus, because no differences were detected.